Activity of Karamunting Leaf Extract (Rhodomyrtus tomentosa (Aiton) Hassk) as an Antibiofilm on Klebsiella pneumoniae - Tia Sabrina; Ricardo Simanjuntak; Erizka Rivani; Rima Zanaria; Evi Lusiana (Jurnal Kesehatan, 2025)
Klebsiella pneumoniae can cause serious infections. The use of antibiotics is often an option in treating infections, but bacteria can adapt by forming biofilms. Therefore, the search for alternative antibiofilms from natural sources is important. One potential plant is karamunting leaves (Rhodomyrtus tomentosa (aiton) hassk). This study aims to describe the potential of the ethanol extract of karamunting leaf as an antibiofilm against Klebsiella pneumoniae. This study is an in vitro descriptive laboratory test. A thick ethanol extract of karamunting leaves was then prepared in three concentration variations: 62.5µg/mL, 125µg/mL, and 250µg/mL. The positive control used was meropenem, and the negative control used was DMSO. The parameter measured for the inhibition and eradication test was biofilm thickness, which was read using a 590nm Microplate reader. In this study, the percentage of inhibition in the three concentrations was 90.65% at a concentration of 250 µg/ml, 86.69% at a concentration of 125µg/ml, and 87.22% at a concentration of 62.5µg/ml. During the eradication test, the percentages obtained were -10.67% at a concentration of 250µg/ml, 3.58% at a concentration of 125µg/ml, and 68.23% at a concentration of 62.5µg/ml. The ethanolic extract of karamunting leaves demonstrates good biofilm inhibitory activity against Klebsiella pneumonia at all tested concentrations. At a concentration of 62.5µg/ml, the extract exhibits good biofilm eradication activity, while at 125µg/ml and in the positive control, it shows poor activity. Interestingly, at a concentration of 250µg/ml, the extract acts as a biofilm promoter, enhancing biofilm formation.